NATIONAL AWARD IN CARDIOLOGY "PURPLE HEART" WILL BE BESTOWED TO THE BEST CARDIAC SURGEON (Столичная издательская компания, 2016)
National Award in Cardiology "Purple heart" will be Bestowed to the best Cardiac Surgeon.